Glimpsing paths: feminist philosophical insights - Gebara, Ivone (2021)
This text has a pedagogical philosophical purpose in the face of current challenges and the pandemic situation. The author indicates that the predominant responses of accusation and pressure from the State or a large religious institution to be loving are not the most effective. It starts, then, from the experiences and thought of the Bolivian sociologist Silvia Rivera Cusicanqui in the Aymara world. The path of micropolitics suggested by Rivera proposes another logic: minimalist, of everyday life (time to create life and changes), of dignified survival that breaks the capitalist logic and survives by bothering the owners of the world. In this sense, from a feminist pedagogical exercise, the author denounces a simplistic vision and analysis in the face of the necessary changes and warns about the urgency of reviewing the epistemological and ethical limits as a condition to follow the search and the common path of humanity and the planet.